Mother, A Symbol of Love And Affection: Peirce Semiotic Study In Lughat Al-‘Aalam Song Lyrics - Salamah, Nur; Sopian, Asep; Nurmala, Mia (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
A song is a communication tool that combines musical instruments with language designed to elicit an emotional response from the soul, evoking moods such as joy, sadness, love, and anger. Foreign lyrics are often difficult to understand by listeners who do not understand the language, which hinders the understanding of the meaning and message conveyed by the author. The objective of this research is to conduct an analysis on the significance of Humood Alkhudher's Lughat Al-'Alam by employing Peirce's semiotic approach. Qualitative methods, specifically content analysis, will be utilized to examine the signs within the song's lyrics, employing Peirce's trichotomy as the analytical framework. The research findings indicate that the verses in these lyrics exemplify a comprehensive comprehension of the numerous privileges bestowed upon mothers in various facets of life, including their manifestation of tenderness, provision of safety, and bestowal of irreplaceable kindness. The use of language and symbols in the lyrics reflects the emotional relationship between a mother and child as well as the diversity of "mother" calls from various cultures as a symbol of respect and affection. The researcher's findings underscore the importance of appreciating the role of a mother and the message of love and warmth contained in the lyrics of Lughat Al-’Aalam. Abstrak Lagu merupakan alat komunikasi yang menggabungkan instrumen musik dengan bahasa yang dirancang untuk menimbulkan respon emosional jiwa, membangkitkan suasana hati seperti kegembiraan, kesedihan, cinta, dan kemarahan. Lirik berbahasa asing seringkali sulit dipahami oleh pendengar yang tidak mengerti bahasa tersebut sehingga menghambat pemahaman makna dan pesan yang disampaikan penulis. Tujuan dari penelitian ini yaitu untuk menganalisis makna dari Lughat Al-‘Alam karya Humood Alkhudher dengan pendekatan semiotik Pierce. Metode kualitatif dengan konten analisis digunakan untuk menganalisis tanda-tanda dalam lirik lagu ini dengan pisau analisis dari trikotomi Pierce. Hasil penelitian menunjukkan bahwa bait-bait dalam lirik ini memperlihatkan pemahaman tentang keistimewaan seorang ibu dalam berbagai aspek kehidupan seperti kelembutan, keselamatan, dan kebaikan yang tidak tergantikan. Penggunaan bahasa dan simbol dalam lirik mencerminkan hubungan emosional antara seorang ibu dan anak serta keragaman panggilan “ibu” dari berbagai budaya sebagai simbol nilai penghormatan dan kasih sayang. Temuan peneliti menggarisbawahi pentingnya menghargai peran seorang ibu dan pesan cinta dan kehangatan yang terkandung dalam lirik lagu Lughat Al-’Aalam.